Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Magnetic field effects on methane–air combustion and emissions in an optical constant volume combustion chamber - Jhe-Kai Lin; Son Hoang Do; Wei-Cheng Wang; Chun-Hao Chiu; Po-Wei Chen; Thong Duc Hong (Fuel, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Synergistic transition binary metal oxide with multiwalled carbon nanotubes interfaces enabling sensitive electrochemical detection of preservative agent diphenylamine - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Rajalakshmi Sakthivel; Ting-Yu Liu; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Laminar nanofiltration composite membranes based on two-dimensional aluminum-tetrakis(4-carboxyphenyl)porphyrin (Al-TCPP) nanosheets for efficient dye/salt wastewater treatment - Shao-Ju Lu; Chun-Po Hu; Chien-Chieh Hu; Chia-Her Lin; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Journal of Environmental Chemical Engineering, 2026)

Parylene-C templated synthesis of hierarchical bismuth nanoflowers for reversible chloride-ion storage - Sanjay Ballur Prasanna; Jian-Lin Lyu; Yu-Lin Lee; Ren-Jei Chung; Hong-ming Ku; Po-Chun Chen (Chemical Engineering Journal, 2026)

Redox-active flower-like ZnMoO4 decorated on 2D graphene oxide nanohybrid as an efficient catalyst for sensitive electrochemical detection of a nitrofuran derivative in environmental and biological matrices - Amulya Garadi; Sanjay Ballur Prasanna; Po-Chun Chen; Gagankumar Sakleshpur Kumar; Nandini Nataraj; Yu-Chien Lin; Xinke Liu; Ting-Yu Liu; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Impact of PM2.5 exposure on gut microbiota abundance and composition in chronic disease patients - Yi-Hsueh Liu; Po Peng; Wei-Chun Hung; Ping-Hsun Wu; Chun-Chi Lu; Yi-Hsiung Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (Air Quality, Atmosphere & Health, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Beyond tractography in brain connectivity mapping with dMRI morphometry and functional networks - Jui-To Wang; Ching-Po Lin; Huei-Min Liu; Carlo Pierpaoli; Chun-Yi Zac Lo (Brain Structure and Function, 2025)
Traditional brain connectivity studies have focused mainly on structural connectivity, often relying on tractography with diffusion MRI (dMRI) to reconstruct white matter pathways. In parallel, studies of functional connectivity have examined correlations in brain activity using fMRI. However, emerging methodologies are advancing our understanding of brain networks. Here we explore advanced connectivity approaches beyond conventional tractography, focusing on dMRI morphometry and the integration of structural and functional connectivity analysis. dMRI morphometry enables quantitative assessment of white matter pathway volumes through statistical comparison with normative populations, while functional connectivity reveals network organization that is not restricted to direct anatomical connections. More recently, approaches that combine diffusion tensor imaging (DTI) with functional correlation tensor (FCT) analysis have been introduced, and these complementary methods provide new perspectives into brain structure–function relationships. Together, such approaches have important implications for neurodevelopmental and neurological disorders as well as brain plasticity. The integration of these methods with artificial intelligence techniques have the potential to support both basic neuroscience research and clinical applications.

Design and Biomechanical Evaluation of a Disposable Eccentric Curette for Effective Necrotic Bone Removal in Core Decompression Surgery - Yu-Kuan Lin; Hsuan-Wen Wang; Po-Kuei Wu; Chun-Li Lin (Journal of Medical and Biological Engineering, 2025)
Purpose Osteonecrosis of the femoral head (ONFH) requires effective removal of necrotic tissue to improve surgical outcomes. Conventional curettes often fail to address clinical needs due to limitations in cutting capability, strength, and adaptability. This study introduces a disposable multi-angle eccentric curette designed to enhance necrotic bone removal during core decompression surgery. Methods The curette was designed with a stainless head featuring wavy cutting edges and oblique grooves for efficient cutting and debris removal. An eccentric rotation mechanism enabled adjustable scraping radii through incremental rotations (60°/120°/180°), forming an inverted bowl-shaped removal area. Performance was evaluated through static torsional strength and dynamic abrasion tests, along with usability assessments by seven orthopedic surgeons. Results The curette achieved average maximum torque of 849.72 ± 50.57 N-cm, exceeding the clinical benchmark of 640 N-cm. Dynamic testing over 300 simulated cycles demonstrated stable cutting performance and precise scraping, with diameter deviations remaining within acceptable limits (initial: 1.05%, final: 5.75%). Usability feedback highlighted its practicality and ease of operation, achieving a satisfaction rate of 97.6%. Conclusion This innovative design addresses critical limitations of existing tools by offering enhanced strength, adaptability, and cutting efficiency. These findings validate the curette’s potential to improve ONFH surgical outcomes.

Exploring the causal relationships between environmental factors and benthos distributions in an intertidal algal reef ecosystem via a structural equation model - Chun-Wei Wu; Shih-wei Liao; Showe-Mei Lin; Shou-Chung Huang; Chang-Po Chen; Po-Kang Shih; Hwey-Lian Hsieh (Continental Shelf Research, 2025)

Selective precipitation of calcium phosphate, N-struvite, and K-struvite from raw seawater for resource recovery - Thi-Hanh Ha; Nicolaus N.N. Mahasti; Hiep-Quang Ha; Po-Lin Liao; Yao-Hui Huang; Ming-Chun Lu (Journal of Water Process Engineering, 2025)

Ion mitigation and strain regulation with 2D Semi-Metals for MA-Based perovskite materials in highly efficient solar cells - Chintam Hanmandlu; Soumallya Banerjee; Abhishek Kumar; Zeeshan Alam Ansari; Ramesh Kumar; Yen-Yu Wang; Lin- Chyn Yuan; Shenghan Li; Raman Sanker; Chandra Shekar Gantepogu; You-Yun Wen; Shyam Narayan Singh Yadav; et al. (Chemical Engineering Journal, 2025)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

3D Effect and countermeasure of 2D geoelectrical imaging of a subsurface linear structure - Yin-Chun Hung; Haoran Wang; Po-Lin Wu; Hsin-Chang Liu; Chih-Ping Lin (Engineering Geology, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Demystifying the interconnections among natural resources, fintech, green technologies, and sustainable environment in E-7 nations - Hsiao-Hsien Lin; Chao-Chun Hsu; Po-Hsuan Wu; Chih-Chien Shen; Gan-Hong Chen (Resources Policy, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Short-term Medication Effects on Brain Functional Activity and Network Architecture in First-Episode psychosis: a longitudinal fMRI study - Yajuan Zhang; Qiong Xiang; Chu-Chung Huang; Jiajia Zhao; Yuchen Liu; Ching-Po Lin; Dengtang Liu; Chun-Yi Zac Lo (Brain Imaging and Behavior, 2023)

Role of auxin in the symbiotic relationship between Piriformospora indica and rice plants - Po-Chun Lin; Ian Lilananda; Ko-Hsuan Shao; Han-Yi Wu; Shu-Jen Wang (Rhizosphere, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Dynamic Regulation of Ions and Amino Acids in Adult Asian Hard Clams Meretrix lusoria Upon Hyperosmotic Salinity - Chia-Hao Lin; Po-Ling Yeh; Yu-Chun Wang; Tsung-Han Lee (Frontiers in Marine Science, 2021)
The dynamic regulation of ions and amino acids in the gills and mantle of the Asian hard clam, Meretrix lusoria , following the exposure to a hyperosmotic environment was hitherto unclear. The present study revealed that the osmolality as well as the Na + and Cl – concentrations in the hemolymph were significantly increased 3 h after transferring the clams from an environment with the salinity of their natural habitat (brackish water; BW; 20‰) to one with hyperosmotic salinity (seawater; 35‰). In addition, we found that the specific activities of Na + /K + -ATPase, a key enzyme that plays a significant role in cell osmoregulation, in the gills and mantle of clams were significantly increased at 72 and 12 h post-transfer, respectively, during acclimation to hyperosmotic salinity. Similarly, the contents of free amino acids (FAAs) such as taurine, alanine, and glycine were significantly elevated during hyperosmotic salinity acclimation. Previous research indicates that taurine is the most abundant FAA in the gills and mantles of Asian hard clams and that the taurine transporter (TAUT) plays an important role in taurine accumulation. The present study showed that TAUT mRNA and protein expression were significantly and transiently increased in the mantle of Asian hard clams following exposure to seawater; although the expression of TAUT mRNA in the gills of Asian hard clams was also transiently stimulated by exposure to hyperosmotic salinity, the relative TAUT protein abundance decreased only at later stages. Accordingly, the findings of this study improve our understanding of the dynamic processes of ion and amino acid regulation in the peripheral tissues of bivalves under hyperosmotic stress.

Combination of XGBoost Analysis and Rule-Based Method for Intrapartum Cardiotocograph Classification - Pao-Lin Kuo; Lim Bee Yen; Yi-Chun Du; Po-Fan Chen; Pei-Yin Tsai (Journal of Medical and Biological Engineering, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

A Novel Assessment of Baroreflex Activity Through the Similarity of Ternary Codes of Oscillations Between Arterial Blood Pressure and R–R Intervals - Po-Wei Chen; Chun-Keng Lin; Wei-Min Liu; Yu-Chen Chen; Sheng-Tzung Tsai; An-Bang Liu (Journal of Medical and Biological Engineering, 2020)

Typical gene expression profile of pseudorabies virus reactivation from latency in swine trigeminal ganglion - Hai-Hua Wang; Jie Liu; Lin-Tao Li; Huan-Chun Chen; Wan-Po Zhang; Zheng-Fei Liu (Journal of NeuroVirology, 2020)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Effect of different ethanolic concentrations on antioxidant properties and cytoprotective activities of Platostoma palustre Blume - Kuan-Hung Lin; Ming-Chih Shih; Po Wang; Yi-Ping Yu; Chun-Ping Lu (Natural Product Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

TRPV4 Activation Contributes Functional Recovery from Ischemic Stroke via Angiogenesis and Neurogenesis - Chun-Kai Chen; Po-Yuan Hsu; Tzu-Ming Wang; Zhi-Feng Miao; Ruey-Tay Lin; Suh-Hang H. Juo (Molecular Neurobiology, 2017)

Hydrology Drives Vegetation Succession in a Tidal Freshwater Wetland of Subtropical Taiwan - Hsing-Juh Lin; Chun-Han Huang; Gwo-Wen Hwang; Chorng-Bin Hsu; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2016)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Elucidation of susceptible factors to endoplasmic reticulum stress-mediated anticancer activity in human hepatocellular carcinoma - Po-Cheng Chiang; Jui-Ling Hsu; Ting-Chun Yeh; Shiow-Lin Pan; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)